Consensus report: Definition and interpretation of remission in type 2 diabetes. Issue 3 (30th August 2021) - Riddle, Matthew C.; Cefalu, William T.; Evans, Philip H.; Gerstein, Hertzel C.; Nauck, Michael A.; Oh, William K.; Rothberg, Amy E.; le Roux, Carel W.; Rubino, Francesco; Schauer, Philip; Taylor, Roy; Twenefour, Douglas
Abstract: Improvement of glucose levels into the normal range can occur in some people living with diabetes, either spontaneously or after medical interventions, and in some cases can persist after withdrawal of glucose‐lowering pharmacotherapy. Such sustained improvement may now be occurring more often due to newer forms of treatment. However, terminology for describing this process and objective measures for defining it are not well established, and the long‐term risks versus benefits of its attainment are not well understood. To update prior discussions of this issue, an international expert group was convened by the American Diabetes Association to propose nomenclature and principles for data collection and analysis, with the goal of establishing a base of information to support future clinical guidance. This group proposed "remission" as the most appropriate descriptive term, and HbA1c <6.5% (48 mmol/mol) measured at least 3 months after cessation of glucose‐lowering pharmacotherapy as the usual diagnostic criterion. The group also made suggestions for active observation of individuals experiencing a remission and discussed further questions and unmet needs regarding predictors and outcomes of remission.